2016
DOI: 10.1016/j.brainres.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the threshold: How NMDAR antagonists induce homeostasis through protein synthesis to remedy depression

Abstract: Healthy neurons have an optimal operating range, coded globally by the frequency of action potentials or locally by calcium. The maintenance of this range is governed by homeostatic plasticity. Here, we discuss how new approaches to treat depression alter synaptic activity. These approaches induce the neuron to recruit homeostatic mechanisms to relieve depression. Homeostasis generally implies that the direction of activity necessary to restore the neuron’s critical operating range is opposite in direction to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…or saline for western blot analysis. The hippocampi were collected within the initiation phase (30 min post injection), a phase where molecular changes facilitate increased downstream mTORC1 activity 11 . Consistent with rapid antidepressants, acute ethanol injection increased the protein expression of GABA B R2 by ∼37% in the hippocampus with no significant change in GABA B R1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…or saline for western blot analysis. The hippocampi were collected within the initiation phase (30 min post injection), a phase where molecular changes facilitate increased downstream mTORC1 activity 11 . Consistent with rapid antidepressants, acute ethanol injection increased the protein expression of GABA B R2 by ∼37% in the hippocampus with no significant change in GABA B R1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that antidepressant efficacy requires two phases—an induction phase and a sustained phase 10 11 . Notably, GABA B R-mediated, mTORC1-dependent protein synthesis is required for the long-lasting sustained phase of rapid antidepressants.…”
mentioning
confidence: 99%
“…Ketamine action in abstinence-associated negative affect While the specific anti-depressive mechanisms of ketamine and other rapid anti-depressants are being actively investigated (for review see: [34][35][36]), pre-clinical studies have suggested that antagonism of GluN2B containing NMDARs with Ro-25-6981 decreases depressive-like behavior in the force swim test [16,37,38], NSFT [31,37,38], and novelty-induced hypophagia [22]. In addition, another GluN2B-NMDA receptor antagonist, ifenprodil, has been shown to reverse chronic unpredictable stress-induced sucrose preference deficits [39].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 24 represents this possible explanation for how the hypothesis of over-inhibition in the PFC fits with reports of GABAergic deficits in stress and affective dysfunction, though this remains to be tested. It has been suggested that rapid-acting antidepressants like ketamine re-engage homeostatic plasticity to elevate both glutamatergic and GABAergic systems again and restore proper E/I balance (Raab-Graham et al, 2016;Workman et al, 2018). In support of this idea, mice deficient for the γ2 subunit of the GABAAR, which show emotional dysfunction, show suppressed glutamatergic and GABAergic system activity, both of which are restored by ketamine treatment (Ren et al, 2016).…”
Section: Integrating Over-inhibition With Gabaergic Deficitsmentioning
confidence: 99%